Whole exome sequencing-based homologous recombination deficiency test for epithelial ovarian cancer - Ying-Cheng Chiang; Hsien-Neng Huang; Kuan-Ting Kuo; Wuh-Liang Hwu; Po-Han Lin (Journal of Ovarian Research)
Abstract Background The homologous recombination deficiency (HRD) test is an important tool for identifying patients with epithelial ovarian cancer (EOC) benefit from the treatment with poly(adenosine diphosphate-ribose) polymerase inhibitor (PARPi). Using whole exome sequencing (WES)-based platform can provide information of gene mutations and HRD score; however, the clinical value of WES-based HRD test was less validated in EOC. Methods We enrolled 40 patients with EOC in the training cohort and 23 in the validation cohort. The WES-based HRD score was calculated using the scarHRD software. We first evaluated the concordance of the HRD status defined by the Myriad MyChoice CDx and then assessed the value of HRD on clinical prognosis in patients with EOC. Results The HRD score defined by the WES-based test was positively correlated with that of the Myriad MyChoice® CDx test (r = 0.82, p < 0.01) in the training cohort. In compared to HRD status of Myriad test, the sensitivity, specificity, positive predictive value, and negative predictive value of the WES-based HRD test were 93.5% (29/31), 77.8% (7/9), 93.5% (29/31), and 77.8% (7/9), respectively. Patients with positive HRD status defined by WES-based scarHRD test and Myriad MyChoice® CDx test were both highly associated with platinum sensitive response (both Fisher’s exact test, p = 0.002) as well as the superior progression-free survival (both log-rank p = 0.002). The multi-variate Cox regression model incorporated with optimal debulking surgery showed that the recurrence risk was decreased in the patients with positive HRD status, either defined by Myriad MyChoice® CDx test (Hazard ratio (HR) 0.33, 95% confidence interval (CI) 0.14–0.79, p = 0.013) or WES-based test Myriad MyChoice® CDx test (HR 0.34, 95% CI 0.14–0.80, p = 0.014). Nine patients had mutations in the genes involved in HR DNA repair, and all of them were positive for HRD. In the validation group, 23 patients were defined as positive HRD by WES-based testing. Six positive HRD patients and 5 negative HRD patients received maintenance PARPi. The median responsive interval of PARPi was 17 months in positive HRD patients and 3 months in negative HRD patients. Conclusion The WES-based test is a potential option for determining the HRD status in EOC patients, and desires for further validation in large-scale cohorts.